PENDIDIKAN AQIDAH DALAM KITAB SHAHIH BUKHARI - Askolan Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2016)
The primary mission of the Prophet Muhammad. is preachedaqidah/monotheism to his people. Aqidah education cored growth, appreciationand practice of Islam in the real sense. Aqidah is a major foundation in theformation of the human person completely. Education that leads to the formationof private tauhid is the first thing to do, because it will underpin the stability ofthe whole human kepribdian. It is seen that Imam Bukhari put a special chapteron aqidah in his book. Imam Bukhari approach laid special chapter on aqidah,indicates that the problem aqidah is something very important in the life ofMuslims.Keywords: Pendidikan Aqidah, Shahih Bukhari.